1930
DOI: 10.1172/jci100275
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Circulatory Actions of Digitalis and Strophanthus With Special Reference to the Liver, and Comparisons With Histamine and Epinephrine

Abstract: In a previous paper (1) it was shown that digitalis in dogs caused a fall in venous pressure at the time when the minute volume flow of blood was diminished. This fall in venous pressure, and hence in return flow of blood to the heart, was correlated with a peripheral vasocontrictor action of the digitalis. It was indicated that constriction of the hepatic veins was the major factor in causing a redistribution of blood, with pooling in the splanchnic area. This venous action of digitalis agreed with results on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0
1

Year Published

1930
1930
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 4 publications
1
8
0
1
Order By: Relevance
“…The increase in liver volume was particularly suggestive, for this indicated a pooling of the blood in this viscus due to diminished outflow as the result of hepatic vein constriction. The constriction of these veins, which are richly endowed with smooth muscle, is strictly consistent with the arterial constrictions in the leg and intestine, and would result in lowered venous pressure.2 The constriction of liver veins by digitalis has been demonstrated by Lampe (29) and confirmed by us (30).…”
supporting
confidence: 65%
“…The increase in liver volume was particularly suggestive, for this indicated a pooling of the blood in this viscus due to diminished outflow as the result of hepatic vein constriction. The constriction of these veins, which are richly endowed with smooth muscle, is strictly consistent with the arterial constrictions in the leg and intestine, and would result in lowered venous pressure.2 The constriction of liver veins by digitalis has been demonstrated by Lampe (29) and confirmed by us (30).…”
supporting
confidence: 65%
“…It had been suggested that the primary action of digitalis is extracardiac (1)(2)(3) and that the direct effects on the vascular bed may be responsible, in part, for its therapeutic action (4). However, in most studies, attention has been directed to the powerful positive inotropic action of this drug (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Dock and Tainter (3,4) believe that an explanation of this sort must be rejected because it fails to take into account the behavior of the rest of the circulatory apparatus which, as they think, is simultaneously affected. They have drawn attention (4) to a mechanism in the hepatic veins by which, under the influence of digitalis, the lumina, the walls containing smooth muscle which contracts, diminish and prevent the return of blood to the heart (10) because it is dammed back into the intestinal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that in their experiments "a fall in venous pressure regularly accompanied the diminished cardiac output " they regard as " convincing evidence that the change in blood flow was a result of peripheral, and not cardiac, actions of the drug " (Conclusion 3) (3). Tainter and Dock (4) showed later that " the fall in right auricular pressure, after giving digitalis to dogs with the hepatic circulation intact, was due to diminished venous return flow, and ultimately to an accumulation of blood in the splanchnic or portal region as a result of obstructed hepatic outflow (hepatic vein constriction).…”
mentioning
confidence: 99%
See 1 more Smart Citation